Laser in medicine : the official journal of European Medical Laser Association (EMLA) for study, research and application of laser in medicine, surgery and dentistry (Laser Medico, 2012)
Časopis sa člancima o istraživanjima i primjeni lasera u medicini, kirurgiji i stomatologiji.